Developing the content of a locomotor disability scale for adults in Bangladesh: A qualitative study - Mahmud, Ilias; Clarke, Lynda; Ploubidis, George B. (BMC, 2022)
This article was published in the Archives of Physiotherapy [© The Author(s). 2017 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/) ] and the definite version is available at : https://doi.org/10.1186/s40945-017-0035-7 The Journal's website is at: https://archivesphysiotherapy.biomedcentral.com/articles/10.1186/s40945-017-0035-7#citeas